A systemic review of clinical trials of COVID-19, registered in WHO-ICTRP - Vyas, Suyog; Vyas, Kartiki S. (International Journal of Clinical Trials, 2020)
In September 2004, International Commission of Medical Journal Editors implemented a dramatic and important policy for the condition of publication of clinical trials. The condition was that clinical trials must be registered in a public trial registry. World Health Organization-International Clinical Trials Registry Platform (WHO-ICTRP) is the globally centralised network composed of primary registries and partner registries along with data providers. COVID-19 is a pandemic and a significant social and economical health burden. In this event numbers of trials have been undertaken by the medical professionals and research workers in every part of the world. Here we have analysed registered clinical trials for the detection, treatment and prevention of COVID-19 to provide a summary of global response w.s.r.to WHO-ITCRP. The objective of this study was to collect the data of registered clinical trials for the therapeutic and preventive measures for COVID-19 which are registered in WHO-ICTRP and analyse global response of COVID-19. WHO-ITCRP database has 20 fields of mapping. Out of these, we have analysed 6 fields of this registry, for this study purpose: public title, scientific title, study type, countries, intervention and primary outcome. Clinical trials are focused on chloroquine, hydroxychloroquine, lopinavir ritonavir combination, Remdesivir, Favipiravir, Tocilizumab and Interferon. Also, it is seen that convalescent plasma therapy is a promising intervention. Observational trials are directed mainly on the clinical features and distinguish COVID-19 from other influenza like illnesses.